What demons can do to saints - Unger, Merrill Frederick, 1909- (Chicago : Moody Press, 1991)
If you're a Christian, you are nose to nose with Satan and his millions of demons. Like it or not, you're in their cross hairs. This book was written to wake up a largely sleeping church. We can't hope to win the spiritual war against fallen angels if we don't know it's being fought or are ignorant of the resources every saint has IN CHRIST to guarantee personal protection and victory.
Originally published: Chicago : Moody Press, 1977.
Includes bibliographical references (p. 217-222).
Keywords: Demonology; Occultism -- Religious aspects -- Christianity